A Writer Development Group for Master’s Students: Procedures and Benefits - Haas, Sarah (Journal of Academic Writing, 2011)
This paper outlines the procedures used in, and evaluates the success of, a pilot writers’ group for MA-level academic writers. After some background on writers’ groups is provided, the activities used in a pilot Writer Development (WD) Workshop, along with the rationale behind the activities, will be described. The usefulness of the activities will then be evaluated from the viewpoint of the student-writers. Results indicate that along with social and affective benefits, the members perceived academic merit in being involved in the group. Most members experienced, at the very least, a heightened awareness of individual writing processes, and of feedback practices and preferences. The activities in the workshops seemed to help the members develop themselves as writers, and an improvement in the quality of written product was perceived by the writers themselves.